Synthesis of (1R, 4R)-2, 5-diazabicyclo[2.2.1]heptane derivatives by an epimerization–lactamization cascade reaction. Issue 14 (19th February 2015) - Cui, Benqiang; Yu, Jie; Yu, Fu-Chao; Li, Ya-Min; Chang, Kwen-Jen; Shen, Yuehai
<x xml:space="preserve">Abstract</x> An epimerization–lactamization cascade of functionalized (2S, 4R)-4-aminoproline methyl esters is developed and applied in synthesizing (1R, 4R)-2, 5-diazabicyclo[2.2.1]heptane (DBH) derivatives.